2019
DOI: 10.1056/nejmoa1815408
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Gene Therapy Combined with Low-Dose Busulfan in Infants with SCID-X1

Abstract: BACKGROUND Allogeneic hematopoietic stem-cell transplantation for X-linked severe combined immunodeficiency (SCID-X1) often fails to reconstitute immunity associated with T cells, B cells, and natural killer (NK) cells when matched sibling donors are unavailable unless high-dose chemotherapy is given. In previous studies, autologous gene therapy with γ-retroviral vectors failed to reconstitute B-cell and NK-cell immunity and was complicated by vector-related leukemia. METHODS We performed a dual-center, phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
170
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(175 citation statements)
references
References 31 publications
1
170
0
3
Order By: Relevance
“…Adverse events caused by insertional mutagenesis of gammaretroviral vectors [13][14][15][16] have resulted in the development of lentivirus-based clinical trials for patients with SCID. Notably, mutagenesis has not been reported in the latter, 5,17,18 but it is still important to continue to explore and develop new therapeutic strategies.…”
mentioning
confidence: 99%
“…Adverse events caused by insertional mutagenesis of gammaretroviral vectors [13][14][15][16] have resulted in the development of lentivirus-based clinical trials for patients with SCID. Notably, mutagenesis has not been reported in the latter, 5,17,18 but it is still important to continue to explore and develop new therapeutic strategies.…”
mentioning
confidence: 99%
“…In the last decade, gene therapy trials based on the infusion of autologous gene-corrected HSCs performed in X-linked SCID and adenosine deaminase (ADA)-SCID as well as in Wiskott-Aldrich syndrome demonstrated the safety and efficacy of this strategy. [2][3][4] T-cell differentiation occurs in the thymus; thus, it has been hypothesized that intrathymic injection of HSCs or progenitors would improve T-cell output and reconstitution in patients with SCID and combined immunodeficiency (Fig 1, A). In preclinical models of SCID and ZAP-70 deficiency, it was indeed shown that intrathymic injection of bone marrow progenitors is a safe procedure and represents an effective strategy to generate protective T-cell immunity.…”
mentioning
confidence: 99%
“…3). In a recent publication on a multicenter study of SCID X1 (Mamcarz et al, 2019), the combination of mild chemotherapy with use of a SIN IL2RG LV vector resulted in the reconstitution of T cell, NK cell, and (to a lesser extent) B cell function in seven of the eight treated patients, with a follow-up period of ≤21 mo. These preliminary results are encouraging in terms of both safety and efficacy.…”
Section: Gene Therapy For Scid X1: Stepmentioning
confidence: 97%